MATLAB GUI 기반 GPS RINEX 관측 파일 생성 소프트웨어의 개발 - 김동욱; 윤호; 한덕화; 장주영; 기창돈; 소형민; 이기훈; 장재규; Kim, Dong-uk; Yun, Ho; Han, Deok-hwa; Jang, Joo-young; et al. (한국항행학회논문지, 2015)
This paper introduces development of the MATLAB GUI based software for generating GPS RINEX observation file. The purpose of this software is to generate GPS measurements of reference station or dynamic user, which are similar to the real GPS receiver data, accurately and efficiently. This software includes two data generation modes. One is Precision mode which generates GPS measurements as accurate as possible using post-processing data. The other is Real-time mode which generates GPS measurements using GPS error modeling technique. GPS error sources are calculated on the basis of each data generation mode, and L1/L2 pseudorange, L1/L2 carrier phase, and Doppler measurements are produced. These generated GPS measurements are recorded in the RINEX observation version 3.0 file. Using received GPS data at real reference station, we analyzed three items to verify software reliability; measurement bias, rate of change, and noise level. Consequently, RMS error of measurement bias is about 0.7 m, and this verification results demonstrate that our software can generate relatively exact GPS measurements. 본 논문에서는 MATLAB GUI 기반으로 개발된 GPS RINEX 관측 파일 생성 소프트웨어에 대해서 소개한다. 개발된 소프트웨어는 두 가지 데이터 생성 모드를 기반으로 기준국 혹은 동적 사용자의 실제 GPS 측정치와 유사한 L1/L2 의사거리, L1/L2 반송파 위상, 도플러 측정치를 정확하고 효율적으로 생성한다. 생성된 측정치 결과는 최종적으로 RINEX version 3.0 관측 파일로 출력된다. 본 논문에서는 소프트웨어 검증을 위해 기준국의 실측 데이터를 기반으로 측정치 바이어스, 변화율, 잡음 수준을 분석해보았다. 그 결과 개발된 소프트웨어가 실제 GPS 측정치와 RMS 약 0.7 m 수준의 바이어스 오차를 갖는 GPS 측정치를 생성함을 확인하였다.